2004
DOI: 10.1016/j.femsle.2004.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Expression of glutathioneS-transferase and peptide methionine sulphoxide reductase inOchrobactrum anthropiis correlated to the production of reactive oxygen species caused by aromatic substrates

Abstract: Peptide methionine sulphoxide reductase (MsrA) and glutathione S-transferases (GSTs) are considered as detoxification enzymes. In the xenobiotics-degrading bacterium Ochrobactrum anthropi the two enzymes are co-induced by toxic concentrations of aromatic substrates such as phenol and 4-chlorophenol. In aerobic organisms, degradation of aromatic substrates by mono- and dioxygenases leads to a generation of oxidative stress that causes the occurrence of reactive oxygen species (ROS). A capillary electrophoretic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 40 publications
1
58
0
1
Order By: Relevance
“…Many of the noncatabolic proteins that were more abundant during growth on biphenyl and/or benzoate versus succinate appear to be associated with a stress response. Oxidative stress may originate from the dioxygenases' activity, which can produce reactive oxygen species (5,36). Four proteins that were more abundant during growth on the aromatic compounds have been linked to oxidative stress responses: the general stress protein GroEL (5,6,15); HslU (25), which degrades abnormal proteins; and AhpCF (4,21,31), which detoxifies peroxides; and a serine kinase (38).…”
mentioning
confidence: 99%
“…Many of the noncatabolic proteins that were more abundant during growth on biphenyl and/or benzoate versus succinate appear to be associated with a stress response. Oxidative stress may originate from the dioxygenases' activity, which can produce reactive oxygen species (5,36). Four proteins that were more abundant during growth on the aromatic compounds have been linked to oxidative stress responses: the general stress protein GroEL (5,6,15); HslU (25), which degrades abnormal proteins; and AhpCF (4,21,31), which detoxifies peroxides; and a serine kinase (38).…”
mentioning
confidence: 99%
“…The most striking effect was observed for AtuGST1 where tetracycline induced an approximately 19-fold increase in transcripts accumulation. A possible role for bacterial GSTs in the protection against the toxic effect of the antimicrobial agents has been suggested previously (Favaloro et al 2000;Veal et al 2002;Tamburro et al 2004;Alias and Clark 2007). For example, studies on the interaction of PmGSTB1-1 with a number of antimicrobial agents indicated that this enzyme was able to sequester antibiotics with avidity (Casalone et al 1998;Allocati et al 2008).…”
Section: Discussionmentioning
confidence: 89%
“…Several abiotic stresses and chemicals are known to affect the expression of GSTs at the transcriptional level (La Roche and Leisinger 1990;Cummins et al 1999;Tamburro et al 2004;Alias and Clark 2007); therefore, transcript accumulations for AtuGST genes were determined in normal culture conditions as well as in response to various xenobiotics, antimicrobial agents and other stress conditions. Gene expression analysis suggested that AtuGSTs genes are induced in a wide range of functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPS cluster includes homologs for sigmaE-regulated algA and algD. SigmaE-regulated pyoverdin synthesis genes as described by Ravel (42); in the latter two, an increase of reactive oxygen species due to oxygenase activity was measured. The stress responses observed in the wild-type cells, except for that involving the PrkA serine kinase, seemed to be mitigated in the mutant strains.…”
Section: Discussionmentioning
confidence: 99%